first wild record of Bulbophyllum lemniscatoides confirms its occurrence in the Philippine archipelago with notes on its habitat and conservation status - Naive, Mark Arcebal K. (Universidad de Costa Rica, 2022)
Bulbophyllum lemniscatoides Rolfe is a species native to Peninsular Malaysia, Thailand, Laos, Cambodia, Vietnam, Sumatra, Java, and Borneo. It was recently collected in Mt. Timolan Protected Landscape of Zamboanga del Sur, confirming its occurrence in the Philippine archipelago. Here, we provide species descriptions based on our collected material and photographs to aid identification, geographical distribution information, habitat, phenology, and an IUCN conservation assessment.